2007
DOI: 10.1158/1535-7163.mct-07-0048
|View full text |Cite
|
Sign up to set email alerts
|

Cell type–dependent effects of Polo-like kinase 1 inhibition compared with targeted polo box interference in cancer cell lines

Abstract: Multiple critical roles within mitosis have been assigned to Polo-like kinase 1 (Plk1), making it an attractive candidate for mitotic targeting of cancer cells. Plk1 contains two domains amenable for targeted interference: a kinase domain responsible for the enzymatic function and a polo box domain necessary for substrate recognition and subcellular localization. Here, we compare two approaches for targeted interference with Plk1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…This residue is a direct target of AurkB (27, 28), and as shown in Figure 3A, the Aurk inhibitor VX-680 potently blocked its phosphorylation. Paradoxically, inhibitors of Plk1 have been reported to promote increased phosphorylation of Histone 3 on Serine 10 (29, 30); consistent with this, we observed increased levels of phospho-H3 Ser10 and decreased levels of Serine 46 phosphorylation of TCTP (translationally controlled tumor protein, a direct Plk1 substrate) upon treatment with BI-2536 (Figure 3B and data not shown). These data suggest that inhibitors of Aurora and Polo-like kinases are active in patched mutant tumor cells.…”
Section: Resultssupporting
confidence: 87%
“…This residue is a direct target of AurkB (27, 28), and as shown in Figure 3A, the Aurk inhibitor VX-680 potently blocked its phosphorylation. Paradoxically, inhibitors of Plk1 have been reported to promote increased phosphorylation of Histone 3 on Serine 10 (29, 30); consistent with this, we observed increased levels of phospho-H3 Ser10 and decreased levels of Serine 46 phosphorylation of TCTP (translationally controlled tumor protein, a direct Plk1 substrate) upon treatment with BI-2536 (Figure 3B and data not shown). These data suggest that inhibitors of Aurora and Polo-like kinases are active in patched mutant tumor cells.…”
Section: Resultssupporting
confidence: 87%
“…In contrast to our results, Liu and Erikson suggested that PLK1 depletion increases Cdc2/cyclin B complex activity in HeLa cells (28). However, Fink et al showed that inhibition of PLK1 activity exerts contrary effects depending on cell type (29). Current studies in our laboratory are underway to explore the signaling pathway modulated by PLK1 in oral cancer cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The predicted human PLK5 is also efficient in inducing G 1 arrest (Fig. 1B), whereas overexpression of the PBD region of Plk1, Plk2, or Plk3 (constructs similar to Plk5-⌬N or PLK5) results in no or minor differences in G 1 arrest (17,22,24) (see Fig. S3 in the supplemental material).…”
Section: Plk5 Is An Antiproliferative Plk Family Member the Murinementioning
confidence: 96%